Modeling systems from partial observations - Champaney, Victor; Amores, Víctor J.; Garois, Sevan; Irastorza-Valera, Luis; Ghnatios, Chady; Montáns, Francisco J.; Cueto, Elías; Chinesta, Francisco (Frontiers in Materials, 2022)
Modeling systems from collected data faces two main difficulties: the first concerns the choice of the measurable variables that will define the learnt model features, and that should be the ones concerned by the addressed physics, optimally neither more nor less than the essential ones. The second concerns the accessibility to data, because generally only limited parts of the system are accessible for performing measurements. This work revisits some aspects related to the observation, description and modeling of systems that are only partially accessible.